Kajian Cemaran Bakteri Patogen Pada Produk Olahan Ikan - Dewi Sartika; Sri Hidayati; Hardianti Fitriani (Jurnal Penelitian Pertanian Terapan, 2019)
Fish proccessed product is a favorite food that contain high protein in Indonesia, such as, otak-otak ikan. The aim of this research was to observe of phatogen bacteria contaminant on fish proccessed product, ex. Salmonella sp., Escherichia coli and Staphylococcus aureus. This research was had done on food proccessed product, used random sampling technicque, at traditional markets. The result data was arranged with descriptive statistic. The result research showed that contaminant of Escherichia coli was 1.54 x 102 colony/ ml at Tani market; 0.3 x 101 colony/ml at Gudang Lelang market. Fish proccessed product was contaminated by Salmonella, too. This research found that Fish proccessed product at Tamin, Tani and Rajabas was Salmonella contaminant detected. The Fish proccessed product that content the highest level of Stahpylococcus aureus were at Tugu narket (1,07 x 102 colony/ml) and Gudang Lelang market (1,12 x 102 colony/ml).